-(x+4)-2(1+x)=x

Simple and best practice solution for -(x+4)-2(1+x)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+4)-2(1+x)=x equation:


Simplifying
-1(x + 4) + -2(1 + x) = x

Reorder the terms:
-1(4 + x) + -2(1 + x) = x
(4 * -1 + x * -1) + -2(1 + x) = x
(-4 + -1x) + -2(1 + x) = x
-4 + -1x + (1 * -2 + x * -2) = x
-4 + -1x + (-2 + -2x) = x

Reorder the terms:
-4 + -2 + -1x + -2x = x

Combine like terms: -4 + -2 = -6
-6 + -1x + -2x = x

Combine like terms: -1x + -2x = -3x
-6 + -3x = x

Solving
-6 + -3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + -3x + -1x = x + -1x

Combine like terms: -3x + -1x = -4x
-6 + -4x = x + -1x

Combine like terms: x + -1x = 0
-6 + -4x = 0

Add '6' to each side of the equation.
-6 + 6 + -4x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -4x = 0 + 6
-4x = 0 + 6

Combine like terms: 0 + 6 = 6
-4x = 6

Divide each side by '-4'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 8t^2+14t+10=0 | | 9-9a=2-10a | | -30(6x-12)=4-16x | | 309/6 | | 2/3(x+5)=1/4(5x-3) | | b=2/3(h-1) | | 4.11x+5=6.6+3.71x | | y/16+8=4 | | (4n-3n^3)-(3n^3-4n)= | | 7+2(x+1)=9+2x | | x^2+10x=250 | | 1-4x=3x+16 | | 12n^2+8n^3+6n= | | 10.6-9.6z+3.8=2.9 | | (a-4)/2-(5(a-4))/8=(5a+20)/4 | | -7=x/5 | | 4x+1+3x+2+2x+3+x+4=10x+10 | | (13x-8)+58=180 | | 16-4x=x+11 | | -3x-8=21 | | 40/n=8/5 | | x^2+200x+12500=0 | | 0,4x-2/3=x/5+1 | | 11.4/19 | | 5[1-2w]+8w=15 | | -6(a+9)+7=3a+2(4a-1) | | -10n+12n=n+2 | | 18x1/6 | | 13a+2=6(a-2) | | 306/6 | | b=3(h-1) | | 5/3/3/5 |

Equations solver categories